Enhancing EFL Reading Comprehension and Engagement through Multimodal Instructional Design: A Convergent Mixed-Methods Study - Riansih, Rismar; Arsyad, Safnil; Adnan, Zifirdaus (FKIP Universitas Lampung, 2025)
Enhancing EFL Reading Comprehension and Engagement through Multimodal Instructional Design: A Convergent Mixed-Methods Study. Objectives: This study explores to what extent the multimodal features incorporated into Indonesian high school English textbooks impact students’ engagement and comprehension during reading. As students engage more and more with visually oriented, digitally mediated texts, it becomes imperative to understand how multimodal materials can shape learning. Method: